The 7 habits of highly effective people : powerful lessons in personal change (Simon & Schuster, 2020)
These 7 habits have become famous and are integrated into everyday thinking by millions and millions of people. Why? Because they work! With Sean Covey's added takeaways on how the habits can be used in our modern age, the wisdom of the 7 habits will be refreshed for a new generation of leaders. With penetrating insights and practical anecdotes, Stephen R. Covey reveals a step-by-step pathway for living with fairness, integrity, honesty, and human dignity - principles that give us the security to adapt to change and the wisdom and power to take advantage of the opportunities that change creates.